Religia chrześcijańska, prawo, państwo - Wójcik, Stanisław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The paper attempts to demonstrate that an upstanding and just state cannot be built exclusively upon the codified law. State and law ought to emerge from a universally accepted tradition and human morality. Personalists believe that morality in politics stems from Chritianity, and that it constitutes a significant argument for a bright future of state and nation.